Unusual Direct Use Projects in Iceland - Lund, John W. (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1988)
Iceland, with a large geothermal resource, has developed three unusual direct use projects. Specifically adapted to their areas and needs, these projects serve important functions. Iceland, striving to become energy independent, provides much of its energy needs from geothermal and hydroelectric sources. Over 80% of the population enjoy the use of geothermal district heating (hitaveita). Greenhouse heating, swimming pool heating, industrial curing, and fish farming are other geothermal applications. The three projects in this article, illustrate how geothermal energy is used directly on site, or transported where none is available